If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7h-16=47
We simplify the equation to the form, which is simple to understand
7h-16=47
We move all terms containing h to the left and all other terms to the right.
+7h=+47+16
We simplify left and right side of the equation.
+7h=+63
We divide both sides of the equation by 7 to get h.
h=9
| (x-3)-(2x-7)+6=13(x-1)+4(2x+1)-7x | | 2(5x-4)-5(x-3)=2x-2(4-2x) | | 6x-4(-x+10)=x+41 | | 2(3x+4)=4(x-6) | | X=-3y+16 | | 3(x+6)+x=2(x+9)+2 | | -4.3-0.1(g)=-6.1 | | 10*0-6y=-60 | | 2ln(x+9)+3ln(5x+6)= | | 90-x=12+2(90-x) | | y=x+3-x+4+x | | 5-4x-7=2x | | 8p+5r= | | 180-x=-12+2(90-x) | | .99x+100=1 | | 90-x=-12+2(90-x) | | 2.4t-2.1t-2.3=7.6 | | 12=x^3 | | 2b-5=23 | | 33=-8r+9 | | 2y=-4x-4 | | 5x-6=6x-4x | | 6t-1=4t+16 | | 8x-115=2x-5 | | 6+65x=39x+24 | | 12x^3+2x^2-18x-3=0 | | 7x-3(4x-1)=0 | | -10=3/4(4h-8) | | 3n-9=n+11 | | x^3-x^2-2x-30=0 | | 3y=-3x+21 | | 7+8x=-14+x |